2011
DOI: 10.1111/j.1549-8719.2011.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microcirculation: A Target for Developmental Priming

Abstract: There is increasing evidence that the early life environment, of which nutrition is a key component, acts through developmental adaptations to set the capacity of cardiovascular and metabolic pathways, and ultimately the limits to physiological challenges in later life. Suboptimal maternal nutrition and fetal growth result in reduced microvascular perfusion and functional dilator capacity, which are strongly associated with later development of obesity, type 2 diabetes, and hypertension. These conditions are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 145 publications
(164 reference statements)
0
30
0
Order By: Relevance
“…56 Such results at least suggest that our preceding discussion on the effects of aging on collateral function, although focusing on animal and in vitro studies, likely applies to humans.…”
Section: Effects Of Aging On the Collateral Circulation Of Humansmentioning
confidence: 93%
“…56 Such results at least suggest that our preceding discussion on the effects of aging on collateral function, although focusing on animal and in vitro studies, likely applies to humans.…”
Section: Effects Of Aging On the Collateral Circulation Of Humansmentioning
confidence: 93%
“…The role of the intrauterine environment, particularly maternal nutrition, in influencing fetal growth and cardiovascular health in offspring in later life is known as the thrifty phenotype hypothesis. In a recent review on this subject, Clough and Norman showed that suboptimal maternal nutrition and fetal growth result in reduced microvascular perfusion and functional reserve capacity, which are strongly associated with later development of obesity, type 2 diabetes and hypertension. They highlighted the fact that these conditions are linked to microvascular rarefaction and remodeling that together limit capillary recruitment, reduce exchange capacity, increased diffusion distances for metabolic substrates, and increased local and overall peripheral resistance.…”
Section: Atherosclerosis In Fractal Pathophysiology; An Ill‐adaptive mentioning
confidence: 99%
“…It permeates the capillary wall (4), which for vessels, consists only of endothelium and its basement membrane. The freed oxygen travels towards the mitochondria in the muscle tissue, by which it will be consumed for adenosine triphosphate generation (2). In muscle tissue, the protein myoglobin is also present, which stores up to one oxygen molecule and releases this if the oxygen demand is very high (3).…”
Section: Assessment Of Microvascular Oxygen Exchange Capabilitymentioning
confidence: 99%
“…The microvasculature is characterized by vessels of diameter smaller than approximately 150 mm, whose primary function is the delivery of nutrients and oxygen to the tissue. However, if the vascular structure changes, for instance through vessel rarefication, peripheral vascular resistance may increase and/or tissue oxygen delivery may be impaired [2]. To understand the dependence between physiological factors and disease a large body of research has been conducted using a wide range of vascular beds and disease models.…”
Section: Introductionmentioning
confidence: 99%